O papel do corpo na comunicação da redução de danos - Oliveira, Marcella de (2022)
This dissertation presents as a theme a discussion about the communication potential of the body in harm reduction programs to people who use psychoactive substances. Its object is the body sensitized with dances of somatic approach, understood as one of the possible strategies to reduce damage related to drug use. The exploratory study is detailed in the methodology of dances with somatic approach, developed in the reports of interventions with artistic-pedagogical workshops in public health services, social assistance and education, with different age groups, socioeconomic contexts, purposes of use and psychoactive scans used among the populations that make up the quorum of the activities performed. The hypothesis is that the harm reduction program can be worked as a creative process, which seeks to root its possibilities of permanence considering the adaptability of the strategies it elects. The main theoretical references are Katz and Greiner (2005; 2015), supporting the synonym of body as corpomedia (Katz, 2005; 2006; 2011; 2021); Neves (2010) and Sigman (2017), to treat body processes and dance methodology with somatic approach; and Salles (1998; 2008), to support the discussion about the creation process. To support the epistemological field of drug use, Carneiro (2019), Sodelli (2016) and Silveira Campos (2019) collaborate, while Lemke (2019) supports the biopolitical perspective, and Schwarcz (2019), the links to the drivers of inequalities in Brazil. In mid-writing, mapping the national political support on drugs, indicating important historical moments for prohibitionist and absenteeist perpetration, the timeline of the construction of the legal context on drugs is reported, which delimits who is included and how, in the programmatic actions promoted. The dissertation also highlights the communicational aspect of the Series Altered State (2020), of Folha de São Paulo, which deals with drug policies